Assessing the Education and Training Needs of Nebraska’s Public Health Workforce - Grimm, Brandon L.; Johansson, Patrik; Nayar, Preethy; Apenteng, Bettye A.; Opoku, Samuel; Nguyen, Anh (Frontiers in Public Health, 2015)
Introduction In 2012, the Great Plains Public Health Training Center (Grant #UB6HP22821) conducted an online survey of state and local health departments and the American Indian (tribal clinics, tribal health departments, and urban Indian clinic) public health workforce across three professional levels. The objectives of the needs assessment were to determine the competency levels of the state’s public health workforce, assess gaps in public health competencies, identify public health training interests, needs, and preferences, and to determine the barriers and motivators to participate in public health training. Methods The assessment was developed using the Council on Linkages Between Academia and Public Health Practice, Core Competencies for Public Health Professionals survey (1). The final assessment was created and piloted by numerous individuals representing practice and academia. Results Respondents identified cultural competency and communication skills as the two most important public health competency domains. Although the public health professionals perceived that they were least proficient in the area of policy development and program planning, participants identified the greatest needs for training in financial planning and management skills and analytical/assessment skills. In general, respondents preferred instructor-led interactive training sessions offered as onsite multi-day workshops or computer-based courses. Respondents identified obesity, health disparities, physical activity, chronic diseases, and diabetes as the top five public health topical areas. Conclusion These priorities align with State and National public health plans. The findings of the needs assessment were used to tailor educational opportunities to build the capacity of Nebraska’s public health system. Additionally, the results were used to develop workforce development plans for numerous local health departments throughout Nebraska.